Factors Associated with Condom Use among a Sample of Men Who Have Sex with Men (MSM) Residing in Rural Oklahoma. Issue 13 (9th November 2020) - Giano, Zachary; Kavanaugh, Katherine E.; Durham, André R.; Currin, Joseph M.; Wheeler, Denna L.; Croff, Julie M.; Hubach, Randolph D.
ABSTRACT: Public health literature often neglects populations from rural communities, particularly with men who have sex with men (MSM). Although HIV/STI infections are decreasing slightly, there is an increase within rural MSM, thus opening the door for further research on condom use behavior in a rural context. In-depth interviews were conducted with 40 MSM in rural Oklahoma regarding their condom use and sexual behaviors. A qualitative analysis revealed five themes with respect to condom usage: physical discomfort of condoms, relationship trust, usage based on the type of sexual act, substance use, and knowledge of a partner's HIV/STI status. A sixth theme within the context of rural Oklahoma revealed participants' fear of physical/verbal abuse, hesitations seeking medical help due to confidentially issues, and general acknowledgment of the lack of education and resources available. Implications include increasing mobile testing locations and a push for marketing greater confidentially within health service providers.